2017
DOI: 10.1098/rsos.160823
|View full text |Cite
|
Sign up to set email alerts
|

Game-based situation awareness training for child and adult cyclists

Abstract: Safe cycling requires situation awareness (SA), which is the basis for recognizing and anticipating hazards. Children have poorer SA than adults, which may put them at risk. This study investigates whether cyclists' SA can be trained with a video-based learning game. The effect of executive working memory on SA was also studied. Thirty-six children (9–10 years) and 22 adults (21–48 years) played the game. The game had 30 video clips filmed from a cyclist's perspective. Each clip was suddenly masked and two or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In addition, to support learning, a textual description of the potential hazard was given after answering (Moreno and Mayer 2005). The current game was adapted from a game previously developed to improve situation awareness among cyclists (Lehtonen et al 2017).…”
Section: Aims Of the Current Studymentioning
confidence: 99%
“…In addition, to support learning, a textual description of the potential hazard was given after answering (Moreno and Mayer 2005). The current game was adapted from a game previously developed to improve situation awareness among cyclists (Lehtonen et al 2017).…”
Section: Aims Of the Current Studymentioning
confidence: 99%
“…A replication study by Lehtonen, Sahlberg, et al, (2017b) found adults possessed higher-level situational awareness compared to children, however this report did not deliver robust evidence in improving child cyclists’ situational awareness. A follow-up study by Lehtonen, Airaksinen, et al, (2017a) found a learning game could be used to train children (and adult) cyclists’ situational awareness. This is particularly relevant to the child participants who felt the learning game was both educational and fun.…”
Section: Introductionmentioning
confidence: 99%
“…Building on the existing literature, we designed an immersive virtual reality serious game to teach hazard perception to students in technical and vocational secondary education in Flanders. Hazard perception, sometimes called hazard identification [13], refers to one's ability to perceive situations as dangerous, including the perceived level of risk [14].…”
Section: Introductionmentioning
confidence: 99%